Key elements to inspire the Teaching of Finance and Tax Law: Discerning what is fair as a methodology (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
In this paper we aim to suggest tree key elements to inspire the teaching of Public Finance and Tax Law: the role of the common good as teleological criteria, the anthropological point of view in legal interpretation and the convenience of approaching the teaching method to the multidisciplinary nature of public finances and taxes.
Keywords: Teaching Guide; tax system´s role; common good; anthropology in Tax Law; multidisciplinary teaching methodology; distributive justice